Burning mouth syndrome - causes and modern treatment methods - Monika Blicharz; Dominika Miazga; Diana Bartosik-Zielińska; Magdalena Bartosik (Kazimierz Wielki University, 2023)
Introduction and purpose: Burning Mouth Syndrome (BMS) is a chronic painful disorder characterized by a burning or stinging sensation in the oral mucosa. It is a condition that affects a significant portion of the population, and its definition has recently been clarified. BMS can be divided into primary (idiopathic) or secondary forms, depending on the presence or absence of an identifiable cause. Brief description of the state of knowledge: Currently, it is estimated that BMS affects 1 in 1000 people, with women over the age of 60 being particularly susceptible. The exact causes of BMS are not well understood, but research suggests they may have a multifactorial nature, involving neuropathic, endocrinological, and psychosocial factors. BMS symptoms include oral burning, taste disturbances, dry mouth, tingling, and numbness of the tongue. Patients often experience burning sensations on the tongue, palate, gums, lower lip, and throat. In addition to physical symptoms, the condition can lead to sleep disturbances, health problems, and psychological disorders. Diagnosing BMS is challenging and time-consuming. A physician must rule out other causes of symptoms, such as oral infections or nutritional deficiencies. A detailed medical history, intraoral examination, and laboratory tests are necessary for diagnosis. Treating BMS requires the collaboration of multiple specialists, including neurologists, dentists, orofacial pain specialists, and psychologists. Summary: Burning Mouth Syndrome remains poorly understood in terms of its causes and treatment. Patients often experience not only physical discomfort but also psychological issues such as depression and anxiety. Treatment is challenging and often does not provide complete relief. Continued research into this condition is crucial to better understand its nature and find more effective treatment methods. Keywords: BMS, Burning Mouth Syndrome, stomatodynia